Analysis of the impact of Airbnb brand personality on consumer involvement and institutional trust - Antonio Cardoso; Augustçe Paulauskaitçe; Hajar Hachki; Jorge Figueiredo; Isabel Oliveira; Reiville Rêgo; Rui Silva; Galv\~ao Meirinhos (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In this study, Airbnb's brand personality is explored in relation to its effects on consumer involvement and institutional trust. The objective of this paper is to fill a gap in marketing research by building up a solid understanding of the relationship between those constructs in the context of hospitality brands. The results of the study revealed that Airbnb's brand personality is mostly associated with excitement, sincerity, and competence. Brand personality was shown to have effects on both consumer involvement and institutional trust, with competence having the biggest impact on consumer involvement, and institutional trust being under the most significant influence of sincerity. The results of this study present meaningful implications not only for the academic community, but also for marketing specialists focusing on branding strategies in the innovative context of sharing economy businesses.
Keywords: 650; Airbnb; brand personality; brand trust; consumer involvement; institutional trust